Comparative study of potentially toxic nickel and their potential human health risks in seafood (fish and mollusks) from Peninsular Malaysia - Chee, Kong Yap; Al-Mutairi, Khalid Awadh (MDPI, 2022)
Human exposure to highly nickel (Ni)-polluted environments through oral ingestion pathways may cause various pathological effects. This biomonitoring study aimed to assess the human health risk of potentially toxic Ni in 19 species of marine fishes from Setiu (Terengganu) and two popular seafood molluscs (mangrove snail Cerithidea obtusa and cockle Anadara granosa) from the coastal area of Peninsular Malaysia. The Ni levels of the three seafood types were found below the maximum permissible limit for Ni. The Ni target hazard quotient values of all seafood were lower than 1.00 for average and high-level (AHL) Malaysian consumers, indicating no Ni’s non-carcinogenic risk of seafood consumption. It was also found that the calculated values of estimated weekly intake were below than established provisional tolerable weekly intake of Ni for both AHL consumers. It can be concluded that both the AHL consumption of seafood would not pose adverse effects of Ni to the consumers. This study provided a scientific basis for the food safety assessment of Ni and suggestions for risk management of potentially toxic Ni of seafood consumption in Malaysia.